Modern weapons and military equipment for issue 4/2014 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
New radar technology for enhanced air defence missile system Patriot PAC-3 MSE;Precision-guided air bomb AASM debuted on non-French aircraft;Project for the new Latin American training aircraft;Airbus plans to give Eurofighter maritime strike capability;China plans to build domestic carriers by 2017;Boeing revealed details about Phantom Swift for VTOL X-Plane;Iomax offers the concept of a light aircraft Arckangel;"Simplified" version of the NH90 transport helicopter planned;A prototype S-97 helicopter Raider closer to first flight;Russian T-50 PAK-FA in the phase of weapons flight tests;MANPADS Verba entered service with of Russian paratroopers;Iran launched a new version of the Nazeat rocket;Renault presented demonstrator vehicles 6x6 under the designation BMX-01;Israeli IWI offers a new sniper rifle Day .338;Colt showed assault rifle CK901;Aircraft carrier "Vikramaditya" commisioned with the Indian Navy;The patrol ship of the Navy of Montenegro "Kotor" sails again.